Comparative biology of bagworm larvae (Metisa plana) fed on oil palm (Elaeis guineensis) and malabar melastome (Melastoma malabathricum) (Asian Journal of Agriculture, 2025)
Abstract. Anggraini E, Istiqomah H, Irsan C, Herlinda S, Muslim A, Suwandi S. 2025. Comparative biology of bagworm larvae (Metisa plana) fed on oil palm (Elaeis guineensis) and malabar melastome (Melastoma malabathricum). Asian J Agric 9: 472-481. Metisa plana Walker, 1883 (Lepidoptera: Psychidae) is a significant defoliator in oil palm plantations, and the weed Melastoma malabathricum L. (malabar melastome) is believed to act as an alternative host, potentially maintaining pest numbers. This study assessed the comparative biology of M. plana larvae raised individually on oil palm and malabar melastome leaves in a laboratory setting. Recently emerged larvae (n?=?10 per treatment) were observed for leaf area consumption, larval bag form, developmental time, and survival rates. The results indicated that larvae consuming malabar melastome had a substantially greater leaf area consumption during instars 1-3 (up to 11.44?±?0.96?cm²) compared to those fed on oil palm (8.91?±?0.58?cm²; p?
Keywords: Bagworm, host plant suitability, insect larval development, Metisa plana